Aśwamedha Yajña As A Legitimation Legitimation Hegemony Based On Dharma - Made Urip Dharmaputra (Jayapangus Press, 2023)
Writing this article aims to interpret the legitimacy of classical era leadership in the story of Aśwamedhika Parwa. The method used in this study is descriptive qualitative with an interpretive analysis model. This type of research is classified as library research with a study of humanities based on a hermeneutic approach. In general, Aśwamedha Yajña is a symbolic ceremony to strengthen the legitimacy of leadership. Even though there is such an assumption, understanding the importance of symbolic legitimacy has illustrated that Aśwamedha Yajña is an ancient ritual tradition that was commonly carried out by kings in ancient times. To obtain legal legitimacy, there are three ways that can be taken, namely symbolic, procedural and material. Symbolically, legitimacy can be obtained by using values and traditions in society. Procedurally, legitimacy can be obtained through general elections. Materially, legitimacy is carried out by providing material to gain support. Of the three ways, Aśwamedha Yajña belongs to the symbolic and material categories. In the Anugīta Parwa section there is a fable of a golden weasel attending the Aśwamedha Yajña ceremony. The fable is a revolutionary interpolation containing criticism of the large-scale yajña practices. The philosophy of Tri Guṇa Yajña also contributes to providing a narrative about the implementation of yajña which is both abstract and real in religious activities.